2006
DOI: 10.1002/marc.200500807
|View full text |Cite
|
Sign up to set email alerts
|

Batch Emulsion Polymerization of Styrene Stabilized by a Hydrophilic Macro‐RAFT Agent

Abstract: Summary: A well‐defined homopolymer of 2‐(diethylamino)ethyl methacrylate has been synthesized by reversible addition‐fragmentation chain transfer (RAFT) polymerization using (4‐cyanopentanoic acid)‐4‐dithiobenzoate as a chain transfer agent. The corresponding protonated homopolymer with a very reactive dithiobenzoate end group has been used as a water‐soluble macromolecular chain transfer agent in the batch emulsion polymerization of styrene without any surfactant. The reaction leads to a stable latex, as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 26 publications
5
97
0
1
Order By: Relevance
“…[18][19][20] As a solution of the problem, Hawkett and coworkers recently proposed an emulsifier-free reversible addition-fragmentation chain transfer emulsion polymerization method utilizing self-assembly. 21,22 Following this proposal, nitroxide-mediated radical polymerization [23][24][25][26][27][28] and reversible addition-fragmentation chain transfer [29][30][31][32][33][34][35] in emulsion polymerization systems have been successfully studied.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] As a solution of the problem, Hawkett and coworkers recently proposed an emulsifier-free reversible addition-fragmentation chain transfer emulsion polymerization method utilizing self-assembly. 21,22 Following this proposal, nitroxide-mediated radical polymerization [23][24][25][26][27][28] and reversible addition-fragmentation chain transfer [29][30][31][32][33][34][35] in emulsion polymerization systems have been successfully studied.…”
Section: Introductionmentioning
confidence: 99%
“…[77] Among the available controlled/living radical polymerization methods successful and extensively studied methods are 1) nitroxide-mediated polymerization (NMP) [78][79][80][81] , 2) atom transfer radical polymerization (ATRP) [82][83][84][85][86] and 3) reversible addition and fragmentation transfer chain polymerization (RAFT). [87][88][89][90][91] Ionic gelation or coacervation of hydrophilic polymers Polymeric nanoparticles are prepared by using biodegradable hydrophilic polymers such as chitosan, gelatin and sodium alginate. The method involves a mixture of two aqueous phases, of which one is the polymer chitosan, a di-block co-polymer ethylene oxide or propylene oxide (PEO-PPO) and the other is a poly anion sodium tripolyphosphate.…”
Section: Controlled/living Radical Polymerization (C/lrp)mentioning
confidence: 99%
“…Manguian et al [45] used a hydrophilic macro-RAFT agent to form a poly(DEAEMA/H + Cl − )-block-polystyrene stabilizer in situ (Scheme 11). In a similar way, dos Santos et al [46] used PEO-b-P(DMAEMA/H + Cl − )-RAFT as precursors of stabilizers to produce a polystyrene latex which is stable for months under alkaline conditions and also against freeze-thaw cycles.…”
Section: Reversible Addition-fragmentation Transfer (Raft) Polymerizamentioning
confidence: 99%
“…Garnier et al [8] demonstrated that the Scheme 11. Synthetic outline of poly(DEAEMA/H + Cl − )-block-polystyrene stabilizer [45].…”
Section: Surfactant Properties Of Amphiphilic Block Co-polymersmentioning
confidence: 99%